Entomology 311 Lab Manual - Scherr, Melissa; Adams, Daniel; Bullock, Baylee; Open Textbook Library (Open Textbook Library, 2019)
Labs in this book supplement the information gained in lecture, as well as providing some perspective and experience with hands-on applications of ideas in pest management. The labs are presented in week-by-week order, so the pre-labs and reading for week 1 are labeled "Pre-Lab 1" and "Week 1 Reading". Pre-Labs are assignments to be done before lab meets, and will be due at the beginning of Lab. Complete the labs using your textbook, web resources, or the reading assigned for the week. Readings are short 1-3 page "chapters" covering background topics pertinent to the upcoming lab, particular groups of insects/arthropods, or methods used in Pest Management. This should be read before coming to Lab each week. Lab Assignments need to be printed and brought to class so that they can be completed as a group in Lab. It is sometimes helpful to read through the assignment ahead of time to get an idea of the subject matter for the week.
Week 1: Introduction to Collection and Curation -- Week 2: Paleoptera and the Primitive Insects -- Week 3: Coleoptera and Lepidoptera -- Week 4: Orthopteroid Orders -- Week 5: Hemiptera -- Week 6: Pests, Predators, and Parasitoids, Pt. II -- Week 7: Soil Insects -- Week 8: Pollinators -- Week 9: The Human Body Biome -- Insect Collection
In English.
Description based on print resource
Keywords: Biology -- Textbooks